The Influencing Factor of MgAl2O4 on Heterogeneous Nucleation and Grain Refinement in Al Alloy Melts - Lin Yang (Materials, 2020)
Grain refinement using oxide additions is commercially feasible and ecofriendly. MgAl2O4 has a lattice structure similar to Al and small lattice misfits with Al, and it can be an effective nucleation core when it meets certain conditions. In this paper, the influencing factor of MgAl2O4 on heterogeneous nucleation and grain refinement in Al alloys was reviewed in terms of physical force, mass percent, particle size and distribution, heating temperature and duration, interface matching, lattice distortion, and chemical reactions at the liquid/solid interfaces. The existence of in situ MgAl2O4 was necessary for heterogeneous nucleation and grain refinement, and the content of MgAl2O4 was a crucial factor in grain refinement. Physical force highly enhanced heterogeneous nucleation and grain refinement through tuning of the wetting, size, and distribution of MgAl2O4 particles with little content. The heterogeneous nucleation of MgAl2O4 played a vital role in grain size reduction when the content was at a critical value. A single crystal of exogenous MgAl2O4 could also be a potent heterogeneous nucleation substrate for Al and Al−Mg alloys under a casting temperature or a high heating temperature with a short holding time for the small lattice misfits between nucleated-phase Al and the MgAl2O4 substrate, with limited lattice distortion.